ISLAMISASI PERADABAN GLOBAL; DEHEGEMONI NILAI-NILAI UNIVERSALISME - Nurkhalis Nurkhalis (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
The universal truth which is elaborated with liberalism, pluralism, rationalism, modernism, secularism, westernization, hedonism, and et cetera have become physiological striking forces against Muslim community in this modern era. Secular-liberalism has misconceived knowledge, religion, revelation, god and other keywords that define worldview on a civilization. Worldview is a value concept, motor of social change, foundation for understanding reality and scholarly activity, these all are found in Islam. The emergence of dichotomy thought in perceiving Islam in two ways; Islam-history, Islam normative, Islam liberal and Islam literal, objective and subjective truths, textual and contextual thinkings are worldview originated from West tradition. These approaches in turn will render difficulty to conceptualize epistemology of and authority in Islam. Ziauddin Sardar and Ali Syari’ati are two muslim scholars tying to develop the idea ofbuilding an islamic civilization, which is known as islamization of civilization. both reject the advance of west technology to help progress of muslim society. Ismail Raji al-Faruqi even argues that the islamization of islamic civilization must be taken through islamizing the knowledge